Probiotics for children with asthma: a systematic review and meta-analysis - Liu, Yang; Zhang, Yuxiao; Li, Yingna; Zhang, Xiaohu; Xie, Liang; Liu, Hanmin (Frontiers in Pediatrics, 2025)
BackgroundAsthma is a common chronic inflammatory disease affecting children worldwide. While probiotics have been proposed as a potential therapy, their efficacy in pediatric asthma management remains controversial.MethodsA systematic search of PubMed, Web of Science, Embase, Cochrane Central Register of Controlled Trials (CENTRAL) and clinicaltrials.gov was conducted to identify randomized controlled trials (RCTs) from 2014 to 2024 evaluating probiotic interventions in children with asthma. Primary outcomes included asthma exacerbation rates and predicted FEV1%. The risk of bias was assessed using Cochrane guidelines.ResultsOut of 1,361 articles, eight RCTs involving 902 participants were included. Meta-analysis showed probiotics significantly reduced acute asthma episodes with risk ratio of 0.38 (95% CI: 0.26–0.56, p < 0.00001) and improved FEV1/FVC ratios (MD = 5.70, 95% CI: 1.93–9.47, p < 0.003) compared to the control group. Neither FEV1 levels nor school attendance showed significant changes.ConclusionProbiotic supplementation may reduce asthma exacerbations and improve pulmonary function in pediatric asthma. However, heterogeneity across studies suggests the need for further research to determine optimal strains, dosages, and treatment durations. This review establishes groundwork for research and practice by exploring microbial interventions in childhood airway disorders.Systematic Review Registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD42024607569, identifier (CRD42024607569).